TB CO-INFECTION WITH HIV/AIDS: A UNIQUE RADIOLOGICAL PRESENTATION AT LACOR HOSPITAL; A POSTCONFLICT NORTHERN UGANDA. - Kitara, David Lagoro; P., Pirio; D., Acullu; P., Opira C. (African Journal of Infectious Diseases (AJID), 2015)
Background: Tuberculosis (TB) infection is thought to develop at any stage of HIV infection. Pulmonary tuberculosis (PTB) and extra-pulmonary tuberculosis are major complications in HIV/AIDS patients. Tuberculosis is still a diagnostic dilemma in low resource countries, with approximately 68.4% of all active pulmonary cases being negative for AAFBs on sputum. Additionally, it is reported that 46.7% of the active cases have disseminated TB with extra-pulmonary TB; further complicating the diagnosis in post-conflict northern Uganda. We therefore sought to clinically and radiologically characterize the various TB diagnosed in HIV/AIDS patients in this low resource and post conflict environment. Materials and Methods: A prospective cohort study was conducted on 320 sero-positive patients in Lacor Hospital. Clinical features, radiographic and ultrasonographic features of confirmed HIV sero-positive patients with suspected TB co-infection were assessed. Patients were recruited consecutively and the Chest radiographs, thoraco-lumbar and lumbar spine radiographs were taken and analyzed. Trans-thoracic ultrasonography (USS) for justified cases with pleural and pericardial effusion was conducted. FNAB and Tru-cut biopsies were performed for histological confirmation. Cases were followed-up for clinical outcomes (improvement and demise) within 2 months. The ethics and review committee of Gulu University Medical School approved the study and patients who did not meet the inclusion criteria were excluded. Data was analyzed using SPSS 13.0. Results: Atypical Chest x-ray finding included: reticulo-nodular infiltrates (69.7%); hilar and mediastinal adenopathy (40%); pleural effusion (27.5%) and miliary (20.6%). Typical Chest x-ray finding included: Apical reticulo-nodularities and fibro-cavitations (27.5%), and normal Chest x-ray (2.2%). Abdominal Ultrasonographic finding included: porta-hepatis, para-aortic and splenic hilum lymphadenopathy (15.9%); Ascitis (8.1%); TB splenitis (5.3%) and TB nephritis with peri-renal abscess (0.3%). PTB was observed in (53.4%); disseminated TB in (42.2%) and EPTB in (4.4%). Majority (81.9%) of the patients improved and was discharged on DOTS while 18.1% died. Conclusion: Imaging assessment is important adjuvant in HIV/AIDS/TB co-epidemic diagnosis. Early diagnosis and prompt management of TB co-infection ensures longer life and reduce morbidity and mortality.